A Straightforward Route to Potent Phenolic Chain‐Breaking Antioxidants by Acid‐Promoted Transposition of 1, 4‐Benzo[b]oxathiines to Dihydrobenzo[b]thiophenes. Issue 46 (6th October 2015) - Viglianisi, Caterina; Amorati, Riccardo; Di Pietro, Leonardo; Menichetti, Stefano
Abstract: The transformation of simple phenols with limited antioxidant activity into potent chain‐breaking antioxidants was achieved by a three‐step protocol, consisting of the conversion of phenols into 1, 4‐benzo[ b ]oxathiines followed by an unprecedented acid‐promoted transposition to o ‐hydroxydihydrobenzo[ b ]thiophenes, or dihydrobenzo[ de ]thiochromenes, starting from phenols or naphthols, respectively. These derivatives, bearing a benzo‐fused heterocycle with a sulfide sulfur ortho to the phenolic OH, have a rate constant of reaction with alkylperoxyl radicals ( k inh ) comparable to that of α‐tocopherol. A solid rationale for the transposition mechanism as well as for the structure‐antioxidant activity relationship is presented. Abstract : Transform and speed‐up : Simple phenols with limited or no antioxidant activity are easily transformed, in three steps, into potent vitamin E‐like chain‐breaking antioxidants through the acid‐mediated transposition of 1, 4‐benzo[ b ]oxathiine to dihydrobenzo[ b ]thiophene. The products have a rate constant of reaction with alkylperoxyl radicals comparable to that of α‐tocopherol.